A Conceptual Paper on Corporate Social Responsibility among Malaysian Entrepreneurs - Tengku Anis Syafiqah Tengku Jasmi; Nazlina Zakaria; Lily Julienti Abu Bakar (Sustainable Business and Society in Emerging Economies, 2020)
Conflicting views on corporate social responsibility have led to various studies on CSR. However, the previous studies focused mainly on large firms rather than small and medium entrepreneurs. It is important to study corporate social responsibility in the context of small and medium enterprises. This is because any initiatives taken by small and medium enterprises can affect society and the economy due their large contributions. Therefore, this paper provides a view on corporate social responsibility among Malaysian entrepreneurs, mainly small and medium enterprises.